Public history and school: international perspectives - Demantowsky, Marko (De Gruyter Oldenbourg, 2018)
Frontmatter -- Preface -- Contents -- What is Public History -- Public History in the Classroom -- Public History and the School Curriculum: Two South African Case Studies -- Learning, and Understanding of Public History as Part of the Professional Historical Education at German Universities -- The Private Use of Public History and its Effects on the Classroom -- Teaching, Learning, and Understanding of Public History in Schools as Challenge for Students and Teachers -- School as an Institution of Public History -- Imagining the Nation throughout School History Master Narratives -- The German Federal President History Competition. A Public History Occasion -- Public Historians in the Classroom -- History Politics, School, Public History -- History Teaching in the Focus of the Swiss People's Party - The way Policies Take Influence on Schools, too -- National Integration and the Idea of "Zweckrationalität" -- If They are Taxi Drivers - What Are We? Archives and Schools -- Professional Identity and the Public Purposes of History -- The Future of Public History - What Shall We Teach Perspectively? -- The Future of Public History - What Shall We Teach Perceptively: Russian Situation -- The Future of Public History - What Shall We Teach Prospectively? Remarks and Considerations -- The Politics of Public History Education -- About the Authors -- Index
Enthält Literaturangaben und ein Register
Erscheint als Open Access bei De Gruyter
Keywords: Aufsatzsammlung; Geschichtsunterricht; Public History